Teacher's Ability In Applying Adaptive Physical Education Learning To Children With Special Needs - Amirzan Amirzan; Sumarjo Sumarjo; Jafaruddin Jafaruddin; Muhammad Muhammad; M Yahya; Indah Lestari (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
The purpose of this research is to find out. how far is the ability of PJOK teachers at SDLB Pante Raya Bener Meriah Regency in implementing adaptive physical education learning models for CSN students? The population and sample in this study were school leaders, administrative staff, permanent teachers, and honorary staff as well as 26 students of SDLB Pante Raya, the sampling technique in this study used a total sample. The data collection technique used observation, interviews, and questionnaires, while the data analysis used was data collection, data verification, and conclusion drawing. The collected data were processed using descriptive analysis of percentages. The results of this study can be concluded that PJOK teachers at SDLB Pante Raya can carry out adaptive, creative, and fun physical education learning to improve students' physical fitness and SDLB Pante Raya students like and play an active role in every PJOK learning activity carried out in schools. Thus it was answered that in general PJOK teachers understood that adaptive physical education had been implemented, but still needed to improve the ability of PJOK teachers through training/upgrading related to adaptive physical education learning, then in general respondents stated that physical fitness was needed by children with special needs to support them in the following learning at school, then they also stated that students were very fond of exercising.